2012
DOI: 10.1021/ja301042u
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Two-Coordinate Acyclic Silylene

Abstract: Simple two-coordinate acyclic silylenes, SiR(2), have hitherto been identified only as transient intermediates or thermally labile species. By making use of the strong σ-donor properties and high steric loading of the B(NDippCH)(2) substituent (Dipp = 2,6-(i)Pr(2)C(6)H(3)), an isolable monomeric species, Si{B(NDippCH)(2)}{N(SiMe(3))Dipp}, can be synthesized which is stable in the solid state up to 130 °C. This silylene species undergoes facile oxidative addition reactions with dihydrogen (at sub-ambient temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
289
2
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 408 publications
(340 citation statements)
references
References 45 publications
14
289
2
19
Order By: Relevance
“…17c The MSeAr Pr i 4 (M = Li, K) salts were prepared by addition of either LiBu n or K metal to the air-stable triselenine, Se(SeAr Pr i 4 )2 (see Supporting Information). 19 1 H and 13 C NMR spectra were recorded on either a Varian 300 MHz, 400 MHz or a 600 MHz instrument and referenced internally to either protio benzene or trace silicone grease (δ = 0.29 in C6D6). 29 Si NMR spectra were acquired on a…”
Section: General Proceduresmentioning
confidence: 99%
“…17c The MSeAr Pr i 4 (M = Li, K) salts were prepared by addition of either LiBu n or K metal to the air-stable triselenine, Se(SeAr Pr i 4 )2 (see Supporting Information). 19 1 H and 13 C NMR spectra were recorded on either a Varian 300 MHz, 400 MHz or a 600 MHz instrument and referenced internally to either protio benzene or trace silicone grease (δ = 0.29 in C6D6). 29 Si NMR spectra were acquired on a…”
Section: General Proceduresmentioning
confidence: 99%
“…A reaction of compound 8 with B 2 pin 2 was performed under identical conditions to those employed in the synthesis of compounds 10 and 11. Initial inspection of the resultant 1 H and 11 B NMR spectra indicated the generation of a single reaction product (12), which was anticipated to be the result of formal n-BuB(hex) elimination to form a magnesium complex of the catenated [ pinB(Bpin)B(hex)] − anion. Work up and crystallisation of compound 12, however, revealed that this process had produced an isomeric form of the anticipated triborane anion (Scheme 4).…”
Section: -48mentioning
confidence: 99%
“…However, a barrier height of 22.0 kcal/mol is not formidable, especially as the ZN catalysis is usually performed at temperatures greater than 60°C [63,64] (it is well established that reactions with barriers of 20.0-25.0 kcal/mol occur readily at room temperature). [65][66][67] What is more pertinent is the result that the insertion process becomes significantly more preferred in comparison to termination, by more than 12.0 kcal/mol, for every donor case that has been considered. The reason for this marked preference can be understood by a comparison of the insertion and termination transition states.…”
Section: (B) Insertion and Termination Studies With The Mgcl 2 Modelmentioning
confidence: 99%